Climate and taxonomy underlie different elemental concentrations and stoichiometries of forest species: the optimum ``biogeochemical niche'' - Sardans, J; Penuelas, J (PLANT ECOLOGY, 2014)
We previously hypothesised the existence of a ``biogeochemical niche{''} occupied by each plant species. Different species should have a specific elemental composition, stoichiometry and allocation as a consequence of their particular metabolism, physiology and structure (morphology) linked to their optimal functioning under the environmental (abiotic and biotic) conditions where they have evolved. We tested this hypothesis using data from the Catalan Forestry Inventory that covers different forest groups growing under a large climatic gradient. Mediterranean species that occupy hotter-drier environments have lower leaf N, P and K concentrations than non-Mediterranean forest species. Within a determined climatic biome, different species competing in the same space have different elemental compositions and allocations linked to their taxonomical differences and their phenotypic plasticity. Gymnosperms have a proportionally higher elemental allocation to leaves than to wood, higher C concentrations, and lower N, P and K concentrations mainly in the stem and branches than angiosperms. The differences among species are linked to asymmetrical use of different elements, suggesting that the biogeochemical niche is a final expression and consequence of long-term species adaptation to particular abiotic factors, ecological role (stress tolerant, ruderal, competitor), different soil occupations and use of resources to avoid interspecific competition, and finally of a certain degree of flexibility to adapt to current environmental shifts.
Keywords: Biogeochemical niche; C:N; Mediterranean; N:P; Nutrients; phosphorus; Potassium

Influence of land use on soil quality and stratification ratios under agro-silvo-pastoral Mediterranean management systems - Francaviglia, Rosa; Benedetti, Anna; Doro, Luca; Madrau, Salvatore; Ledda, Luigi (Agriculture, Ecosystems & Environment, 2014)
a b s t r a c t A case study from north-eastern Sardinia (Italy) in semiarid conditions is presented. Agriculture is mainly extensive and markedly agro-silvo-pastoral, and is typical of similar areas of the Mediterranean basin. The following land uses at different levels of crop intensification were considered: tilled vineyard (TV), no-tilled grassed vineyard (GV), hay crop and pasture with sparse cork oaks (HC and PA), semi-natural systems (SN, former vineyards set-aside about 30 years ago), cork oak forest (Quercus suber L.) established in the past century (CO). Some soil quality parameters were considered: soil organic carbon (SOC) and total N (TN) concentrations, stocks and their stratification ratios with depth (SRs), microbial biomass carbon (MBC) and its quotient to SOC (qmic), and C:N ratios. Both in terms of concentrations and stocks, SOC and TN were generally higher in HC, PA, CO and SN: in these land uses SOC in the topsoil were in the range 17.0–24.3 g kg−1 and 48.9–65.4 t ha−1; TN values were 1.07–2.08 g kg−1 and 3.1–6.0 t ha−1. SOC and TN SRs under the CO land use were higher than 4, quite above the proposed threshold (?2), >2 in GV, and ≥2.0 in PA. MBC in mg kg−1 and qmic in ?g g−1 were higher under CO (194 and 0.89) and GV (156 and 0.97). C:N ratios had optimum or nearly optimum (9–12) values in CO, PA and the GV, in agreement with the SRs, MBC and qmic. A positive and significant correlation was found between SOC and TN concentrations in all the land uses. ©
Keywords: C:N; mediterranean systems; Microbial biomass; Microbial quotient; Soil organic carbon; Stratification ratio; Total N